Distinct circulating cytokine levels in patients with angiography-proven coronary artery disease compared to disease-free controls - Maaniitty, Eveliina; Sinisilta, Sami; Jalkanen, Juho; Vasankari, Tuija; Biancari, Fausto; Gunn, Jarmo; Jalkanen, Sirpa; Airaksinen, K.E. Juhani; Hollmén, Maija; Kiviniemi, Tuomas (Elsevier, 2025)
Background: Systemic inflammation has a critical role in the development of symptomatic coronary artery disease (CAD). Identification of inflammatory pathways may provide a platform for novel therapeutic approaches. We sought to determine whether there are differences in circulating cytokine profiles between patients with CAD and disease-free controls as well as according to the severity of the disease.
Methods: Case-control study's population consisted of 452 patients who underwent diagnostic invasive coronary angiography due to clinical indications. We measured the serum concentrations of 48 circulating cytokines. Extent of CAD was assessed using the SYNTAX Score in 116 patients. Cytokine differences between groups were tested using Mann-Whitney U test and associations with CAD were explored using a logistic regression model.
Results: Overall, 310 patients had angiographically verified CAD whereas 142 had no angiographically-detected coronary atherosclerosis. In multivariable logistic regression models adjusted for age, sex, hypertension, atrial fibrillation, history of smoking and treatment for diabetes and hyperlipidemia, increased levels of interleukin 9 (OR 1.359, 95%CI 1.046-1.766, p = 0.022), IL-17 (1.491, 95%CI 1.115-1.994, p = 0.007) and tumor necrosis factor alpha (TNF-α) (OR 1.440, 95%CI 1.089-1.904, p = 0.011) were independently associated with CAD. Patients with SYNTAX Score>22 had increased levels of stromal cell-derived factor 1 alfa (SDF-1α), beta-nerve growth factor (β-NGF), IL-3 and decreased level of IL-17 compared to those with score ≤22 when adjusted for smoking and use of beta-blockers.
Conclusions: Patients with CAD have distinct circulating cytokine profiles compared to disease-free controls. Distinct cytokines may have pivotal roles at different stages of coronary atherosclerosis. ClinicalTrials.gov Identifier: NCT03444259 (https://clinicaltrials.gov/study/NCT03444259).